Evaluating the Effects of CBI on an English for Medical Students Program - Kathleen Corrales; César Maloof (Universidad de La Sabana, 2009)
This study investigated the effectiveness of CBI on the development of oral communicative competence and the causes of this development on a Medical English program in an English as a foreign language context. The participants were 16 Colombian university students between the ages of 17 and 22 from various semesters in their academic medical program. The instruments included classroom observations, learning journals, and interviews. The data was analyzed and categorized in light of the research questions. The analysis showed that students developed their oral and discourse skills in English in a relevant, challenging, and meaningful manner because the approach implemented was based on the integration of language and content. Through these materials that served as models for the students, they were able to activate their prior knowledge, lessen anxiety, raise their self-confidence and become motivated towards language learning.